Pengaruh Harga Terhadap Kepuasan Wisatawan dalam Industri Pariwisata - I Wayan Wiwin (UHN IGB Sugriwa Denpasar, 2018)
Price plays an important role in the perception of tourists to the value and quality of tourism industry products. price becomes an important factor in making reservations. This confirms the need for companies in the tourism industry to offer a value proposition is very strong price, which includes superior service. Price has even become a more important part than the perception of quality, this suggests that price satisfaction has a greater effect on loyalty rather than quality. However, it is important to understand that loyalty, which is a product of overall satisfaction (service, quality and price), is associated with tolerance would be more advantageous price. This means that companies with the tourism industry managed to get a tourist satisfaction and loyalty will be more likely to impose higher premiums for the service and experience they offer.